What is the general solution of the differential equation # x^2 (d^2y)/(dx^2) - 3x dy/dx+y=sin(logx)/x #?

Answer 1

# y = Ax^(2-sqrt(3)) + Bx^(2+sqrt(3)) + (5sinlnx)/(61x) + (6coslnx)/(61x) #

We have:

# x^2 (d^2y)/(dx^2) - 3x dy/dx+y=sin(logx)/x # ..... [A]
This is a Euler-Cauchy Equation (the power of #x# is the same as the degree of the differential in every occurrence of their product) which is typically solved via a change of variable. Consider the substitution:
# x = e^t => xe^(-t)=1#

Next up, we have

#dy/dx = e^(-t)dy/dt#, and, #(d^2y)/(dx^2)=((d^2y)/(dt^2)-dy/dt)e^(-2t)#

When we replace the original DE [A], we obtain:

# (e^t)^2 ((d^2y)/(dt^2)-dy/dt)e^(-2t) - 3(e^t) e^(-t)dy/dt+y=sin(loge^t)/((e^t)) #
# :. (d^2y)/(dt^2)-dy/dt - 3dy/dt+y = e^(-t)sint #
# :. (d^2y)/(dt^2) - 4dy/dt+y = e^(-t)sint # ..... [B]
This is now a second order linear non-Homogeneous Differentiation Equation. The standard approach is to find a solution, #y_c# of the homogeneous equation by looking at the Auxiliary Equation, which is the quadratic equation with the coefficients of the derivatives, and then finding an independent particular solution, #y_p# of the non-homogeneous equation.

Complementary Role

The homogeneous equation that goes with it is:

# (d^2y)/(dt^2) - 4dy/dt+y = 0 # ..... [C]

whose Auxiliary Equation is:

# m^2-4m+1 = 0#

This quadratic equation can be solved, and the two distinct real solutions that result are:

# m=2+-sqrt(3) #

Consequently, the solution to the homogeneous equation [C] is:

# y_c = Ae^((2-sqrt(3))t) + Be^((2+sqrt(3))t)#

Specific Resolution

A likely solution for this particular equation [B] is as follows:

# y = ae^(-t)sint + be^(-t)cost # # \ \ = e^(-t)(asint + bcost) #
Where #a# and #b# are constants to be determined. Let us assume the above solution works, in which case be differentiating wrt #x# we have:
# y' \ \= e^(-t)(acost - bsint) - e^(-t)(asint + bcost) # # \ \ \ \ \= e^(-t)( (a-b)cost - (a+b)sint ) #
# y'' = e^(-t)(-(a-b)sint - (a+b)cost ) - e^(-t)((a-b)cost - (a+b)sint ) # # \ \ \ \ \ = e^(-t)(2bsint -2acost) #
Substituting into the Differential Equation #[B]# we get:
# e^(-t)(2bsint -2acost) - 4e^(-t)( (a-b)cost - (a+b)sint ) + e^(-t)(asint + bcost) = e^(-t)sint #
Equating coefficients of #cos(x)# and #sin(x)# we get:
#cos(x): -2a - 4(a-b) + b = 0 # #sin(x): 2b +4 (a+b) + a = 1 #

When we solve concurrently, we obtain:

# a=5/61 # and #b=6/61#

Thus, we arrive at the specific solution:

# y_p = 5/61e^(-t)sint + 6/61e^(-t)cost #

Overall Resolution

which ultimately results in the GS of [B^

# y(t) = y_c + y_p # # \ \ \ \ \ \ \ = Ae^((2-sqrt(3))t) + Be^((2+sqrt(3))t) + 5/61e^(-t)sint + 6/61e^(-t)cost#

Now, in the beginning, we employed a variable change:

# x = e^t => t=lnx #

Restoring this variable change gives us the following:

# y = Ae^((2-sqrt(3))lnx) + Be^((2+sqrt(3))lnx) + 5/61e^(-lnx)sinlnx + 6/61e^(-lnx)coslnx#
# :. y = Ax^(2-sqrt(3)) + Bx^(2+sqrt(3)) + 5/61e^(ln(1/x))sinlnx + 6/61e^(ln(1/x))coslnx#
# \ \ \ \ \ \ = Ax^(2-sqrt(3)) + Bx^(2+sqrt(3)) + 5/61 (1/x)sinlnx + 6/61 (1/x)coslnx #
# \ \ \ \ \ \ = Ax^(2-sqrt(3)) + Bx^(2+sqrt(3)) + (5sinlnx)/(61x) + (6coslnx)/(61x) #

This is [A]'s General Solution.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the general solution of the given differential equation (x^2 \frac{{d^2y}}{{dx^2}} - 3x \frac{{dy}}{{dx}} + y = \frac{{\sin(\log x)}}{x}), follow these steps:

  1. First, we'll rewrite the equation in a standard form, which is a second-order linear homogeneous differential equation: [x^2 \frac{{d^2y}}{{dx^2}} - 3x \frac{{dy}}{{dx}} + y = 0] [x^2 y'' - 3xy' + y = 0]

  2. Next, we'll find the general solution to the homogeneous equation (x^2 y'' - 3xy' + y = 0).

  3. To solve this, we'll assume the solution has the form (y = x^m), where (m) is a constant.

  4. Substitute (y = x^m) into the homogeneous differential equation: [x^2 (m(m-1)x^{m-2}) - 3x(mx^{m-1}) + x^m = 0]

  5. Simplify the equation: [m(m-1)x^m - 3mx^m + x^m = 0] [m(m - 1 - 3 + 1)x^m = 0] [m(m - 3)x^m = 0]

  6. The characteristic equation is (m(m - 3) = 0).

  7. Solve the characteristic equation to find the roots: [m(m - 3) = 0] [m = 0, 3]

  8. Since we have distinct real roots, the general solution to the homogeneous differential equation is: [y = C_1 x^0 + C_2 x^3] [y = C_1 + C_2 x^3]

  9. Now, we'll find a particular solution to the non-homogeneous equation using the method of undetermined coefficients or variation of parameters.

  10. Given the non-homogeneous term (\frac{{\sin(\log x)}}{x}), we'll guess a particular solution of the form (y_p = A \sin(\log x) + B \cos(\log x)).

  11. Substitute (y_p = A \sin(\log x) + B \cos(\log x)) into the non-homogeneous differential equation and solve for (A) and (B).

  12. Once we have (A) and (B), the general solution to the non-homogeneous differential equation is: [y = C_1 + C_2 x^3 + A \sin(\log x) + B \cos(\log x)]

  13. Therefore, the general solution to the given differential equation is the sum of the general solution to the homogeneous equation and the particular solution to the non-homogeneous equation: [y = C_1 + C_2 x^3 + A \sin(\log x) + B \cos(\log x)]

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7